PROCESSING OF FISH PROTEIN CONCENTRATE FROM DRIED FISH BY ACETIC ACID DIGESTION - Ahmed, H. A.; Hindi, M. J.; Alhasson, A. S. (Iraqi Journal of Aquaculture, 2022)
This investigation is aimed at processing fish protein concentrate from dried fish that subjected to digestion with acetic acid at pH 4. The dried fish contained 46.26% protein, 19.65% fat and 23.89% ash. The processed protein product comprised of 69.84% protein, 8.43% fat and 15.58% ash. The yield was 70.15% of raw materials. The processed product characterized with dark brown colour, acceptable fishy smell and revealed high storage stability when stored at room temperature (28°C) for 60 days without noticeable changes. The stored product had low bacterial count that valued 1200 CFU/gm. Coliform bacteria were not existed. Total volatile Nitrogen Bases (TNVB) was low and valued 9.8 mgN/100 gm. Rancidity hadn’t developed as TBA rated 0.24 mg malonaldehyde/kg. The processed product and a commercial protein concentrate were employed separately in formulating experimental diets R1 and R2 respectively. Each ration was used in feeding trials on carp fingerlings for 60 days. The results for R1 and R2 were respectively as follows: 0.77 and 0.51 for specific growth rate (SGR); 4.04 and 5.79 for food conversion ration (FCR); 24.71% and 17.26% for Food conversion efficiency (FCE); 16.56 and 12.23% protein deposit (PD). It can be concluded that the proposed method employed in this project was successful in processing fish protein concentrate with good storage stability and acceptable sensory properties.